(untitled) (Annals of Medical Research, 2021)
Aim: The main factors most frequently associated with Helicobacter pylori (HP) in studies include patient age, poor socio-economic status, and antibiotic use. Limited/inadequate Health Literacy (HL) is also associated with poor health conditions. A possible relationship between HP and HL has not been shown in the literature yet. This study aimed to explore the relationship between HL and HP infection both of which have comparable patient profile.Material and Methods: The study evaluated the data regarding 188 patients who underwent gastroscopy due to the complaint of dyspepsia in cross-sectional analytic design. Health Literacy was evaluated using European Health Literacy Survey Questionnaire (HLS-EU-Q47) scale. The presence of HP was confirmed by histopathological examination.Results: Median age was smaller in the HP-positive group (p=0.001). In Helicobacter pylori-positive patients, mean scores were only high for household and taking part in community activities questions in the HLS-EU-Q47 scale. While 47.20% of the patients in the HP (+) group were smokers, 31.30% of the patients in the HP (-) group were smokers, with a difference between HP groups in terms of smoking status (p=0.026). Conclusion: There was no relationship between HP and HL in this sample. HL probably does not play a role in HP positivity but its prognostic role can be discussed further in prospective studies.